'I wish someone watched me interview:' medical student insight into observation and feedback as a method for teaching communication skills during the clinical years. Issue 1 (December 2016) - Schopper, Heather; Rosenbaum, Marcy; Axelson, Rick
Abstract Background Experts suggest observation and feedback is a useful tool for teaching and evaluating medical student communication skills during the clinical years. Failing to do this effectively risks contributing to deterioration of students' communication skills during the very educational period in which they are most important. While educators have been queried about their thoughts on this issue, little is known about what this process is like for learners and if they feel they get educational value from being observed. This study explored student perspectives regarding their experiences with clinical observation and feedback on communication skills. Methods A total of 125 senior medical students at a U.S. medical school were interviewed about their experiences with observation and feedback. Thematic analysis of interview data identified common themes among student responses. Results The majority of students reported rarely being observed interviewing, and they reported receiving feedback even less frequently. Students valued having communication skills observed and became more comfortable with observation the more it occurred. Student-identified challenges included supervisor time constraints and grading based on observation. Most feedback focused on information gathering and was commonly delayed until well after the observed encounter. Conclusions Eliciting students' perspectives on the effect of observation and feedback on the development of their communication skills is a unique way to look at this topic, and brings to light many student-identified obstacles and opportunities to maximize the educational value of observation and feedback for teaching communication, including increasing the number of observations, disassociating observation from numerically scored evaluation, training faculty to give meaningful feedback, and timing the observation/feedback earlier in clerkships.